2004
DOI: 10.1046/j.1420-9101.2003.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and speciation in the genus Tursiops based on microsatellite and mitochondrial DNA analyses

Abstract: Bottlenose dolphins (Tursiops truncatus) have a world‐wide distribution, and show morphotypic variation among regions. Distinctions between coastal and pelagic populations have been documented; however, regional patterns of differentiation had not been previously investigated in a wider geographic context. We analysed up to nine different populations from seven different areas of the world by mitochondrial DNA and microsatellite DNA markers, and found differentiation among all putative regional populations. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
248
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(281 citation statements)
references
References 47 publications
(75 reference statements)
28
248
2
3
Order By: Relevance
“…In addition, 194 published D-loop sequences of Tursiops truncatus were used to obtain a general picture of population structure in the Atlantic Basin ( Natoli et al 2004). These populations were classified as coastal or pelagic according to the nomenclature adopted in one of the most recent studies (Natoli et al 2004).…”
Section: Acquisition Of Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 194 published D-loop sequences of Tursiops truncatus were used to obtain a general picture of population structure in the Atlantic Basin ( Natoli et al 2004). These populations were classified as coastal or pelagic according to the nomenclature adopted in one of the most recent studies (Natoli et al 2004).…”
Section: Acquisition Of Sequencesmentioning
confidence: 99%
“…Recently, a comprehensive study showed significant differentiation between several coastal populations and two highly polymorphic pelagic populations, one in the north-eastern Pacific and one in the north-western Atlantic (Natoli et al 2004). Some coastal populations appeared to be morphologically and genetically sufficiently distinct to be classified as a separate species, such as T. aduncus in Chinese waters (Wang et al 1999;Wang et al 2000) and a potential third species along the South African coast (Natoli et al 2004). Pelagic forms have been reported to range primarily between the 200-and 2000 m-isobaths (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Absence of genetic structure over hundreds and even thousands of kilometres implies the existence of gene flow over much larger distances than usually documented in small delphinids (e.g., Natoli et al 2004;Escorza-Treviño et al 2005;Parsons et al 2006;Oremus et al 2007). It has long been controversial whether such amounts of gene flow could be achieved through individual long-distance movements.…”
Section: Discussionmentioning
confidence: 94%
“…South Pacific spinner dolphins, Stenella longirostris, Oremus et al 2007) or ecological specialisation in relation with habitat features (e.g. killer-whales, Orcinus orca, Hoelzel et al 1998a; common bottlenose dolphins, Tursiops truncatus, Hoelzel et al 1998b;Natoli et al 2004, pantropical spotted dolphins, Stenella attenuata, Escorza-Treviño et al 2005). In the latter case, forms specialised for different habitats (called "ecotypes") are often both genetically and morphologically differentiated (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This great geographical variation has led some authors in the past to divide the genus Tursiops into as many as 20 different species (Hershkovitz, 1966;Rice, 1998). Nevertheless, only two species are currently recognized, T. truncatus, the 'common bottlenose dolphin', and T. aduncus (Ehrenberg, 1982), the 'Indian Ocean bottlenose dolphin' (Wang et al, 1999;2000a, b;Natoli et al, 2004;Wells and Scott, 2009). Recently a third potential species of Tursiops was formally described for southern Australian coastal waters, T. australis, the 'Burrunan dolphin' (Charlton-Robb et al, 2011).…”
Section: Introductionmentioning
confidence: 99%